GE_GERICHTE P/23145/2024 vom 22. Juli 2025 - GE Cour de justice (2025)
LÉSION CORPORELLE GRAVE;TENTATIVE(DROIT PÉNAL);RIXE;AGRESSION;FIXATION DE LA PEINE;SURSIS À L'EXÉCUTION DE LA PEINE | CP.122; CP.133; CP.22; CP.134; CP.47; CP.43